Characteristics of subclinical tuberculosis compared to active symptomatic tuberculosis using nationwide registry cohort in Korea: prospective cohort study - Jeong, Yun-Jeong; Park, Jae Seuk; Kim, Hyung Woo; Min, Jinsoo; Ko, Yousang; Oh, Jee Youn; Lee, Eun Hye; Yang, Bumhee; Ahn, Joong Hyun; Kim, Jin Woo; Hwang, Yong Il; Park, Kwang Joo; et al. (Frontiers in Public Health, 2023)
Objective: The clinical manifestations of tuberculosis (TB) range from asymptomatic to disseminated depending on the microbiological and immunological status, making the diagnosis challenging. To improve our understanding of the disease progression mechanism, we aimed to identify the characteristics of subclinical TB and important predictors of symptom development. Methods: From July 2018 to June 2019, we systemically collected data from the National Surveillance System of South Korea on patients with pulmonary TB, and compared the characteristics of subclinical and active symptomatic TB patients. Results: A total of 4636 patients with pulmonary TB were included, and the prevalence of subclinical TB was 37.1% (1720/4636). In subclinical TB patients, the positivity rates of acid-fast bacilli (AFB) smear and culture were 16.2% and 50.2%, respectively. Subclinical TB patients were younger (55.6±19.2 vs 60.7±19.5, P<0.001), had a higher body mass index (21.7±3.1 vs 21.0±3.5, P<0.001), less under Medicaid support, and had lower rates of chronic lung disease, AFB smear and culture positivity, and bilateral disease. Regarding the characteristic differences of individual TB-related symptoms, age was positively associated with dyspnoea and general weakness but negatively associated with chest pain, haemoptysis, and weight loss. Male patients were more prone to weight loss. Chronic lung disease was related to symptoms including cough/phlegm, dyspnoea, and haemoptysis, while autoimmune diseases were associated with fever and weight loss. Conclusions: The development of TB-related symptoms was associated with microbiological burden and clinical characteristics including underlying comorbidities, which should be evaluated carefully.